Climate Change and Food Security in India: Challenges and Opportunities†. (15th July 2016) - Singh, Gurbachan
Abstract: Achieving food and nutritional security in a scenario of degrading natural resources (water, soil, biodiversity) and climate change seems to be a big challenge. Global warming has triggered the melting of glaciers, sea level rise and submergence of islands/coastal areas, and change in rainfall and temperature pattern over the next century is predicted. Such change is bound to affect water, land and biodiversity patterns which will demand a new set of land‐use patterns including enterprises, commodities, crops and varieties. Effects of climate change have already started impacting on agricultural productivity in several agroclimatic regions and subregions of India. The likely predicted scenario of climate change on agriculture, location‐specific case studies depicting climate change impacts such as drought, cold and heatwaves and required adaptation and mitigation strategies are discussed in this paper. It is emphasized that adaptations of agriculture to climate change will call upon proactive or anticipatory research on enterprises, commodities, crops, varieties and farming systems resilient to cold, heat and moisture stresses. Copyright © 2016 John Wiley & Sons, Ltd.